Réponses

2014-05-31T21:37:34+02:00
A)
-5/4 +x/2= -2 + 3/4  on multiplie par 4 les 2 membres de l'égalité
-5*4/4 +4x/2 = -2*4 + 3*4/4
-5+2x = -8+3
2x = -5+5
2x = 0
x = 0

b)
-x/2=2/3x +7/6  on multiplie par 6 les 2 membres de l'égalité
-6x/2 = 6*2x/3+7*6/6
-3x = 4x +7
4x+3x = -7
7x = -7
x = -7/7
x = -1
  • Utilisateur Brainly
2014-06-01T00:00:29+02:00
- 5/4 + x/2 = - 2 + 3/4 
- 5 + 2x = - 8 + 3 
2x = - 5 + 5
2x = 0
x = 0/2
x = 0


- x/2 = 2/3x + 7/6

- 3x = 4x + 7
4x + 3x = - 7
7x = - 7
x = - 7/7
x = - 1